An overview on precision therapy in bladder cancer. Issue 5 (2nd September 2020) - Sayed, Ahmed; Munir, Malak; Eweis, Noor; Wael, Doaa; Shazly, Omar; Awad, Ahmed K.; Elbadawy, Marihan A.; Eissa, Sanaa
ABSTRACT: Introduction: Bladder cancer is a common global cause of morbidity and mortality, with many patients not responding to -or not tolerating- traditional chemotherapeutic regimens. Recent studies have allowed us to utilize the genetic profile of tumors to better target therapy as is required, as well as innovate novel therapeutic interventions usable when more traditional options prove futile. Areas covered: The development of novel interventions in bladder cancer, particularly immune checkpoint inhibitors, as well as using genetic markers to guide both traditional and novel therapeutic interventions. We also discuss the utility of these markers in diagnosing and prognosticating bladder cancer patients. Expert opinion: Biomarker-guided therapy could revolutionize bladder cancer care in several ways: not only do novel therapeutic agents provide alternate treatment options for more difficult cases, but it can also increase the efficacy of more traditional treatment options. In addition, it may have a role in the early diagnosis and detection of bladder cancer, as well as predicting the course and prognosis of these patients. Unresolved challenges include how to best optimize therapy with novel agents as regarding duration and patient selection, as well as investigations as to whether using gene-guidance results in clinically improved patient outcomes.